Landslide deformation mechanism and stability analysis under earthquake and rainfall conditions: a case study of Shibanping landslide - Wang, Lijuan; Guo, Wanjia; Bai, Shiming; Bian, Rui; Zhang, Liang; He, Zhihao; He, Binbin; Chen, Fujiang; Jing, Juncheng; Gao, Meiben (Frontiers in Earth Science, 2025)
Landslides, as a common geological disaster, pose a significant threat to the safety of people’s lives and property, as well as the stability of infrastructure in mountainous areas. Based on a detailed investigation of the Shibanping landslide, this paper first analyzes the causes and mechanisms of the landslide. Secondly, the plane sliding method and numerical simulation method are adopted to explore the changes in the stability of the landslide under natural, rainfall, and seismic conditions. The research results show that the instability of the Shibanping landslide is closely related to the complex geological structure, topography, geomorphology, lithology, excavation activities, hydrological changes caused by rainfall, and seismic effects in the area. The deformation of the landslide starts with tensile cracking and downward displacement at the top. Then, it gradually expands to the deep layer and the front edge under the influence of rainfall and excavation; its mechanism is progressive-bedding slip. Rainfall increases the self-weight, saturation, and pore water pressure of the rock and soil mass, leading to a continuous decrease in effective stress, thereby exacerbating the instability of the landslide. Earthquakes reduce the stability of the slope through shear stress caused by seismic waves. The stability calculation results indicate that the landslide has a certain degree of stability under natural conditions, but its stability decreases significantly when rainfall or earthquakes occur. This study provides theoretical support for the analysis and prevention of landslide stability, and is of great significance especially for the prediction, prevention, and control of landslides in areas with long-term rainfall and high earthquake frequency.